An Analysis Of Assertive Speech Act On Sentences Used In The Speeches Of Barack Obama - Fitriana, Dasti, Dra. Siti Zuhriah Ariatmi, M.Hum, Dra. Malikatul Laila, M. Hum (2014)
Assertive speech act is concerned with facts which the purpose is to inform. There are six focuses of assertive utterances: on information, on truth-value of utterance, on speaker's commitment or involvement in what is reported, on manner of communicating, on the nature of the message, and focus on aspect. This research aimed at 1) describing the types of assertive speech act which are found in President Barack Obama in His Own Word e-book, 2) describing the illocutionary act of sentences found in President Barack Obama in His Own Word e-book. The data are the speeches of Barack Obama which collected in President Barack Obama in His Own Word e-book. The techniques of data collection is observation and documentation. The technique for analyzing data is descriptive analysis. The study shows that: 1) the focus of assertive utterances based on illocutionary act used in speeches Barack Obama are 27 (36%) focus on information, 34 (45,33%) focus on truth and value of utterance, 6 (8%) focus on manner of communicating, 1 (1,33%) focus on the nature of the message, and 7 (9,4%) focus on aspect. And the last is the illocutionary act of assertive utterance, the writer finds 3 motivating (4%), 2 predicting (2,67%), 25 persuading (34,66%), 8 requesting (10,67%), 11 threatening (14,67%), 9 warning (12%), 4 worrying (5,33%), 2 convincing (2,67%), 1 inviting (1,33%), 1 swearing (1,33%), 2 hoping (2,67%), 1 promising (1,33%), 2 guaranteeing (2,67%), and 3 influencing (4%).